Control of the deposition ratio of Bi2Te3 and Sb2Te3 in a vacuum evaporator for fabrication of Peltier elements - Gonçalves, L. M. (2006)
This article reports the main problem and the corresponding solution of the co-evaporation of Bi2Te3 and Sb2Te3 films for the fabrication of Peltier elements. This main problem consists in the control of the deposition rates of the two elements: Bi or Sb and Te, which have very different vapor pressures. The control of the deposition ratio was achieved by means of a PID controller, which permitted the fabrication of thin-film Peltier elements that produce a temperature gradient in the order of 2C between their hot and cold junctions, when measured at free air conditions.